PERKEMBANGAN KONSEP KRIYA - b muria zuhdi (Imaji, 2003)
Abstract The term kriya, which refers to the art utilizing the materials of crafts Like basket weaving, pottery, etc., can be discussed not only in the context of past art works (referring particularly, in this case, to the classical or traditional works of this art) but also in the context of those that look new and different from the ones from the past. For that reason, this reference to time - past and present - is the point of departure in this article. A reference to time contains a historic aspect. What is meant in this writing is none other than the movement based on the intention of creating art works which are new in character but using as their sources the traditional arts of Indonesia. This is the movement that has eventually given birth to or revived the aforementioned term for the art concerned here, has at the same time distinguished present from past works of this art, and has as simultaneously distinguished those works of art from mere handicrafts. Key Word: kriya